ANTIBACTERIAL ACTIVITY OF BASIL LEAVES EXTRACT TOWARDS BACTERIA STAPHYLOCOCCUS AUREUS AND STAPHYLOCOCCUS EPIDERMIDIS IN DEODORANT SPRAY - Khairani, Tetty Noverita; Fitri, Khairani; Andry, Muhammad; Nasution, Muhammad Amin (Universitas Muhammadiyah Magelang, 2023)
Body odor is a significant problem and is often encountered in some individuals characterized by excessive odor. A deodorant spray made from basil leaf (Ocimum Basilicum L.) extract is a product used to treat body odor caused by Staphylococcus Aureus and Staphylococcus epidermidis bacteria. The purpose of this study is to assess the efficacy of deodorant spray and basil leaf extract on bacterial activity, as well as the optimal dose of deodorant spray for lowering the activity of these bacteria. Method the research was conducted experimentally, testing antibacterial activity using agar diffusion. The results of the deodorant spray preparation test showed that the preparation was homogeneous, organoleptically brown in color, had a distinctive smell, and had a liquid texture; the pH test results met the requirements for deodorant spray 4.5-6.5. The average diameter of the inhibition zones produced from each preparation were Staphylococcus epidermidis bacteria, positive control 7 mm, negative control 10.1 mm; formula 5% 12.3 mm; formula 10% 13.3 mm; formula 15% 12.7 mm maximum concentration in inhibiting bacteria is formula 10% by 13.3 mm, while the bacteria Staphylococcus Aureus positive control 13 mm, negative control 11.2 mm, 5% formula 13.1 mm; formula 10% 13.4 mm; 15% formula 13.9 mm maximum concentration in inhibiting bacteria is 15% formula 13.9 mm. Based on the inhibitory zone created by 10% basil leaf ethanol extract, Staphylococcus epidermidis bacteria had a 13.3 mm clean zone and Staphylococcus aureus bacteria had a 26.5 mm clean zone.